Outdoor Finishing of Intact Male Portuguese Alentejano Pigs on a Sustainable High-Fiber Diet: Impacts on Blood, Growth, Carcass, Meat Quality and Boar Taint Compounds - Martins, José Manuel (2023)
This trial evaluated the effect of sex on the blood, growth, carcass, meat quality, and boar taint compounds in male Alentejano (AL) pigs (n = 30). From ~40 to 130 kg LW, castrated (C) and intact pigs (I and IExp groups) were fed commercial diets ad libitum. Between ~130 and 160 kg (slaughter), C and I pigs continued on commercial diets, while IExp were fed an experimental diet containing locally produced pulses and by-products aimed at reducing boar taint. At ~160 kg, blood urea levels were higher in IExp than C pigs, triacylglycerols were lower in both intact groups, and cortisol was lower in IExp. IExp pigs exhibited faster growth, improved feed conversion ratio, carcass higher commercial yield and leaner meat than C pigs. The loin intramuscular fat in intact pigs was lower, less saturated and more polyunsaturated, while total collagen was higher. Fat androstenone content was higher in intact pigs and skatole content was similar across treatments, although they were below threshold values for consumer detection. Finally, although boar taint compounds were low in intact AL pigs raised outdoors, adding pulses and by-products to the experimental diet did not result in a reduction in fat skatole content compared to pigs fed the commercial diet.